The antinematicidal activity of vitamin E and its derivatives on Sterinernema feltieae - Khairan, Khairan; Idroes, Rinaldi; Murniana, Murniana; Diah, Muhammad (Universitas Syiah Kuala, 2023)
Vitamin E is found naturally in some foods, and also available as a dietary supplement.